2009
DOI: 10.1111/j.1600-079x.2009.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves oxidative stress parameters measured in the blood of elderly type 2 diabetic patients

Abstract: An elevated oxidative status in the aging organism may be involved in the development of non-insulin dependent diabetes mellitus (NIDDM). Melatonin, a potent antioxidant agent, is essential for glucose homeostasis and regulation. The aim of this study was to determine the influence of melatonin supplementation on the oxidative stress parameters in elderly NIDDM patients. The malondialdehyde (MDA) concentration, Cu-Zn superoxide dismutase (SOD-1) activity in erythrocytes, the level of nitrate/nitrite in plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 46 publications
5
52
1
3
Order By: Relevance
“…Melatonin consumption (5 mg/ day for 30 days) in type 2 diabetic patients resulted in a significant rise in SOD-1 activity and a reduction in the MDA level [31]. Moreover, 5 mg/day melatonin supplementation for 30 days in primary essential hypertension patients significantly increased SOD-1 and catalase activity and reduced products of lipid peroxidation [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin consumption (5 mg/ day for 30 days) in type 2 diabetic patients resulted in a significant rise in SOD-1 activity and a reduction in the MDA level [31]. Moreover, 5 mg/day melatonin supplementation for 30 days in primary essential hypertension patients significantly increased SOD-1 and catalase activity and reduced products of lipid peroxidation [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long-term melatonin consumption (4 mg/ kg/day for 16 weeks) in rats started before the establishment of obesity, attenuated weight gain and prevented the development of obesity induced metabolic alterations [21]. In type 2 diabetic patients, 5 mg/day melatonin consumption for 30 days did not alter body weight and BMI [31]. In another clinical trail, 5 mg/ day melatonin supplementation for 2 months for patients with metabolic syndrome did not change the BMI [32].…”
Section: Discussionmentioning
confidence: 99%
“…Profound studies have shown enhanced oxidative stress in both experimental and human diabetes mellitus [35,36] . Increased levels of liver TBARS has been documented well in diabetic rats [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Many herbal extracts or derivatives with high antioxidant activity are useful for treatment of diabetes and other metabolic syndrome [5] . Over production of ROS and insufficient antioxidant defense mechanism were well documented in diabetic patients as well as in experimental diabetes mellitus [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…21 Im pro ve ments of an ti o xi da ti ve de fen se we re ob ser ved af ter me la tonin supp le men ta ti on in NIDDM in di vi du als and me la to nin supp le men ta ti on was sug ges ted as an addi ti o nal tre at ment for the con trol of di a be tic comp li ca ti ons. 21 In our study, re sults of me la to nin tre at ment we re si mi lar with tho se stu di es. Me la tonin re du ced oxi da ti ve im pacts of hypergl yce mi a on the re ti na.…”
mentioning
confidence: 99%